Eco-Friendly Alternatives to Conventional Plastics – Finger Millet Based Soluble Food Folds - Jeyaveeraraghu, Vinodhini; Chinnappan Ambrose Kalpana (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Plastics are rendered as a symbol of this disengagement – a psychological and physical barrier between us and what we consume. People have been involved in preparing and consuming food folds since the 1900s. From the method of making a particular traditional sweet from Atreyapuram, Andhra Pradesh, this study attempted to create folds from ‘Ragi'. The main objective is to create soluble food folds that serve as a versatile bio-packaging unit that is 100% consumable and contributes to zero wastage, which the common womenfolk of community can prepare. Methods: Raw and germinated millets were processed to create edible folds. Subsequently, phytochemical and antioxidant analyses were conducted to evaluate the potential health benefits of the folds. Results and Discussion: Both the folds were relatively compatible to hold the dry contents inside. The highest percentage of scavenging activity is observed for aqueous extract of Germinated ragi fold (G), which scavenged 79.13 % radicals at a 100 Î¼g/ml concentration. The low absorption percentage was expressed by an aqueous extract of Non- Germinated ragi fold (NG), which scavenged 5.22 % radicals at a concentration of 500 Î¼g/ml. However, there is no significant difference between the phytochemical components between folds made from germinated ragi and non-germinated ragi. Conclusion: Edible food folds present a novel strategy for diminishing plastic waste and promoting eco-friendly food habits. Continued research could facilitate widespread acceptance, encouraging a greener approach to food packaging and consumption.